(untitled) (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2015)
This paper analyzes an in-depth case analysis on impact investment in Spain. Momentum Project is an initiative to support social entrepreneurs in their path to growth. The goal is to increase the social return and to help the social enterprises to reach their long-term sustainability. At the beginning, Momentum started as an “accelerator” for social entrepreneurs; however, an impact investment vehicle is created to support the financial needs of the growth plan. The characteristics of the investment vehicle are compared to those of the philanthropic venture capital as studied in the academic literature.